Race and colonialism around 1800: Herder, Fischer, Kleist - Raisbeck, J (Taylor and Francis, 2022)
Herder’s ‘Neger-Idyllen’, Kleist’s Die Verlobung in St. Domingo, and Caroline Auguste Fischer’s William der Neger offer an exploration of the intersection between race and colonialism in the Atlantic World and in Europe around 1800. Teaching students to read depictions of race, violence, and struggles for emancipation does not only engage with the fraught legacies of the Enlightenment, but, practically speaking, it is also an exercise in suspicious reading. Herder’s anti-imperialist and antislavery poems end with an uneasy negotiation of paternalism. Kleist’s novella provides a racially biased narrator, who limits access to the thought processes of non-white characters. Fischer’s short story moves towards upholding an ideal of emancipation, but recoils from its corollary of revolutionary violence, and crafts two images of its protagonist that cannot be reconciled: one of internalized self-hatred, based on racial identity, the other, of a Christ-like saviour for oppressed peoples.